Insomnia Disorder in Adult Attention-Deficit/Hyperactivity Disorder Patients: Clinical, Comorbidity, and Treatment Correlates - Fadeuilhe, Christian; Daigre, Constanza; Richarte, Vanesa; Grau-López, Lara; Palma-Álvarez, Raul F.; Corrales, Montse; Ramos-Quiroga, Josep A. (Frontiers in Psychiatry, 2021)
Introduction: Several investigations have been performed on insomnia symptoms in adult attention-deficit/hyperactivity disorder (ADHD). However, the relationship between insomnia disorder and adult ADHD has been neglected in research. The main objective of the current study is to analyze the differences between adult ADHD patients with and without insomnia disorder, in terms of ADHD clinical severity, medical and psychiatric comorbidity, psychopharmacological treatment and quality of life. Material and method: 252 adult patients with ADHD (mean age 37.60±13.22 years; ADHD presentations: combined: 56.7%; inattentive: 39.7%; hyperactive/impulsive: 3.6%) were evaluated with an exhaustive clinical and psychological evaluation protocol including semi-structured interviews (for comorbidities and ADHD assessment) and symptom rating scales for ADHD. The diagnosis of ADHD and insomnia disorder was made according to DSM-5 criteria. Furthermore, the Pittsburgh Sleep Quality Index, Insomnia Severity Index, and Epworth Sleepiness Scale were administered. Results: Insomnia disorder was found in 44.4% of adult ADHD patients, was more common in combined presentation (64.3%), and in patients with more ADHD severity. Comorbidities (both medical and psychiatric), especially mood disorders (42%), anxiety disorder (26.8%), personality disorder (39.3%), and any substance use disorder (11.6%) were associated with a higher insomnia disorder prevalence. ADHD stimulant treatment was related to lower insomnia disorder compared to patients without medication, as well as ADHD stable treatment. Additionally, worse health-related quality of life was associated with insomnia disorder. Conclusion: Insomnia disorder is highly prevalent in adult ADHD and is related to higher ADHD severity and more psychiatric and medical comorbidities. Some stimulants and stable pharmacological ADHD treatment are associated with better outcomes of insomnia disorder.